Investigation of abrasive waterjet peening process on bending strength and erosion resistance of different ply combination of fibre metal laminate based aluminium-lithium alloy - Syed Qutaba, Tariq (2024)
Fibre metal laminate (FML) composites have been used widely in many applications due to its excellent mechanical properties such as high fatigue and impact resistance as well as high bending resistance and strength. However, the current requirement in aircraft industry requires further improvement in terms of bending and erosion resistance. Peening processes have been used as a surface treatment method to improve the FML properties. Still, the shot peening has limitations in the coverage area and the laser shock peening experiences involvement of high rate of heat during the process. Hence, abrasive waterjet (AWJ) peening can be conveniently used with a more comprehensive coverage of the FML surface and less generation of surface temperature. The objective of the present work is to investigate the effect of abrasive waterjet peening process on the bending strength and erosion resistance and its surface microstructural changes of glass fibre aluminium-lithium laminate reinforced epoxy. The effect of different combination of 3/2 and 4/2 aluminium-lithium alloy and glass fibre sheets on physical and mechanical properties was also investigated. Several peening parameters namely hydraulic pressure, p (69, 97 and 117 MPa), abrasive mesh size, a (80, 120 and 160 #), nozzle standoff distance, d (20, 40 and 60 mm) and number of jet passes, n (1 and 2 passes) were selected for the experimentation. In terms of physical properties, it was found that 4/2 plies FML produced a higher density and thickness because more total number of plies. Meanwhile, 3/2 plies FML resulted in a higher fibre volume fraction since it has lesser number of metallic sheets with the same amount of fibre layers. As a result, tensile and bending strength of 3/2 plies FML were found to be higher as compared to 4/2 plies FML. In terms of the effect of AWJ peening parameters, a higher flexural strength (up to 482 MPa) and a lower surface erosion (up to 3.4 mg) were achieved at medium p, higher a, higher d and multiple n. This constitutes about ± 10% improvement from the original specimen without treatment. In terms of surface microstructural changes, results indicated that the fibre layers hindered the deformation of the aluminium-lithium layer thus increasing the compactness by around 5%. Based on the assessment of scanning electron microscope (SEM) images, it was revealed that the aluminium-lithium layer experienced a severe damage especially at a higher impact intensity of peening process with enlarged surface craters. It can be concluded that the AWJ peening process can improve the flexural strength and erosion resistance of glass fibre aluminium-lithium laminate reinforced epoxy which is advantageous for the application in the aircraft industry